2019
DOI: 10.1515/jpem-2018-0548
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of diabetic ketoacidosis in newly diagnosed type 1 diabetes children in western Saudi Arabia: 11-year experience

Abstract: Background A wide range of reports on the incidence of diabetic ketoacidosis (DKA) at the onset of type 1 diabetes mellitus (T1DM) in children have been published worldwide. Reports from Saudi Arabia are limited. The aim of this study was to assess the incidence, clinical pattern and severity of DKA in children with newly diagnosed T1DM and the association of autoimmune conditions with initial DKA occurrence at King Abdulaziz Medical City – Jeddah. Methods This retrospective chart review was conducted during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 39 publications
2
19
0
1
Order By: Relevance
“…Literature suggests that increased awareness of T1D results in earlier diagnosis and treatment, can lead to DKA rate decrease [8,[33][34][35]. However, awareness publicity campaigns directed to type 1 diabetes have not shown consistent results [24,33,34,[36][37][38][39].…”
Section: Discussionmentioning
confidence: 99%
“…Literature suggests that increased awareness of T1D results in earlier diagnosis and treatment, can lead to DKA rate decrease [8,[33][34][35]. However, awareness publicity campaigns directed to type 1 diabetes have not shown consistent results [24,33,34,[36][37][38][39].…”
Section: Discussionmentioning
confidence: 99%
“…Hence, hyperglycemic crisis and development of DKA can be prevented by good education about diabetes, for both the patient and parents [11,12] DKA incidence at King Abdulaziz Medical City -Jeddah. They have found that the incidence of DKA among those who are newly diagnosed as T1DM pediatric patients was 37.8%, which is a high percentage [13].…”
Section: Discussionmentioning
confidence: 99%
“…Different cities in Saudi Arabia have reported that there is a significant increase in the incidence and prevalence of T1DM in the last 20 years [ 28 , 29 ]. A systematic review in 2017 reported that the number of children with T1DM is 16,100.…”
Section: Menamentioning
confidence: 99%
“…Moreover, this rate of incidence was more likely linked to environmental factors, particularly viral infections, rather than genetic factors. Hence, the authors recommended conducting further epidemiological studies to screen environmental triggers, especially viral infections [ 29 , 30 ]. However, an earlier report in the Eastern region of Saudi Arabia found that there was no relationship between the etiology of T1DM and viral infections, despite the previously noted seasonal pattern of T1DM [ 31 ].…”
Section: Menamentioning
confidence: 99%